Carbon nanotube conductive hydrogel as well as preparation method and application thereof
By preparing nano-carbon tube conductive hydrogel, the problem of the existing technology being difficult to effectively resist multidrug-resistant bacterial infection and promoting infectious wound healing is solved, and excellent antibacterial properties and healing are achieved.
Patent Information
- Application Number
- CN202411626015.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-03-04
AI Technical Summary
The prior art is difficult to effectively resist multidrug-resistant bacterial infections and promotes healing and tissue regeneration of infectious wounds.
Using nano-carbon tube conductive hydrogel, a hydrogel with conductive and biocompatible was prepared by mixing components such as β-CD, gelatin, single-wall carbon nanotubes, N-formyl-Met-Leu-Phe and endothelial cell growth supplements, and after pH adjustment, ultrasound, bubble removal and photocuring treatment.
The hydrogel has excellent antibacterial properties, can effectively resist wound bacterial infection, promote angiogenesis and tissue regeneration, significantly improving the healing effect of infectious wounds.
Smart Images

Figure CN119548671A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hydrogels, and in particular to a nano carbon tube conductive hydrogel and a preparation method and application thereof. Background Art
[0002] Currently, infected wounds affect millions of people worldwide, and treating infected wounds is a major challenge in clinical medicine. Wound healing is a complex and dynamic process involving a series of biological responses triggered by injury responses. Any changes in key processes or components involved in healing may lead to adverse outcomes. In addition, enhancing antibacterial and angiogenic capabilities is one of the most commonly used strategies. The main clinical treatment method is debridement combined with antibiotic therapy. However, long-term or repeated use of antibiotics can easily cause problems such as dysbiosis, superinfection, and increased bacterial resistance. Effective treatment methods will bring great benefits to mankind.
[0003] In addition, bacterial infection is the most common problem encountered during wound healing and skin regeneration. The severe inflammatory response caused by infection not only significantly increases infection-related complications, but also significantly reduces the quality of wound healing. In addition, the treatment of bacterially infected wounds is difficult, the course of treatment is long, and the cost is high, which will cause a huge economic burden on patients and society. The clinical method of mainly using antibiotics to treat infected wounds is not ideal in terms of anti-infection and wound healing due to drug resistance and lack of a suitable skin repair microenvironment. Therefore, how to effectively resist multidrug-resistant bacterial infections and promote infected wound healing and tissue regeneration at the same time is still a major problem that needs to be solved urgently. Summary of the invention
[0004] The purpose of the present invention is to provide a nano-carbon tube conductive hydrogel and a preparation method and application thereof. The nano-carbon tube conductive hydrogel prepared by the method provided by the present invention has excellent antibacterial properties, can resist bacterial infection of wounds, and at the same time has the function of promoting angiogenesis or tissue regeneration, thereby achieving excellent effect of treating infectious wounds.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing a carbon nanotube conductive hydrogel, comprising the following steps:
[0007] (1) mixing β-CD, an organic solvent and triethanolamine, cooling the mixture, adding acrylic acid, and sequentially performing first stirring, filtering and concentrating to obtain a concentrated solution;
[0008] The concentrated solution is dripped into acetone and subjected to post-treatment to obtain acrylic acid-modified cyclodextrin, also known as Ac-β-CD;
[0009] (2) mixing the Ac-β-CD obtained in step (1) with gelatin and PBS to obtain a mixed solution;
[0010] (3) adding an endothelial cell growth supplement and N-formyl-Met-Leu-Phe to the mixed solution obtained in step (2), and shaking to obtain an EF@HGM solution;
[0011] The EF@HGM solution and the single-walled carbon nanotubes are mixed, and an EF@S-HGM solution is obtained by a second stirring;
[0012] (4) The EF@S-HGM solution obtained in step (3) is sequentially subjected to pH adjustment, ultrasonication, debubbling, addition of an initiator and photocuring to obtain a carbon nanotube conductive hydrogel, also known as an EF@S-HGM hydrogel.
[0013] Preferably, in step (1), the ratio of the mass of β-CD to the volume of triethanolamine is 10 g: (3-12) mL.
[0014] Preferably, the post-treatment in step (1) comprises washing and vacuum drying in sequence.
[0015] Preferably, in the step (2), the concentration of gelatin in the mixed solution is 5 to 12 wt %, and the concentration of Ac-β-CD in the mixed solution is 3 to 20 wt %.
[0016] Preferably, the oscillation temperature in step (3) is 34-42° C., and the oscillation time is 6-15 min.
[0017] Preferably, the concentration of single-walled carbon nanotubes in the EF@S-HGM solution in step (3) is 0.5-4 mg / mL.
[0018] Preferably, in step (4), adjusting the pH value is to adjust the pH value of the EF@S-HGM solution to 7.2-7.6.
[0019] Preferably, the light curing in step (4) is performed by irradiating the film under 365 nm ultraviolet light for 8 to 14 minutes.
[0020] The present invention also provides a carbon nanotube conductive hydrogel prepared by the preparation method described in the above technical solution.
[0021] The present invention also provides the use of the carbon nanotube conductive hydrogel described in the above technical solution in the preparation of regenerative medicine materials.
[0022] The present invention provides a method for preparing a carbon nanotube conductive hydrogel. The prepared EF@S-HGM hydrogel is a host-guest supramolecular macromolecule (HGM) hydrogel, which has biocompatibility, can be injected in situ in wounds, and can be rapidly bonded in vitro; its main components include Ac-β-CD, gelatin, single-walled carbon nanotubes (SWCNT), N-formyl-Met-Leu-Phe (FMLP) and endothelial cell growth supplement (ECGS), wherein ECGS can improve the proliferation of vascular endothelial cells and coordinate matrix remodeling in blood vessels, repair wounds, and FMLP can act as a chemokine to bind to specific receptors on the surface of neutrophils, attract neutrophils, and improve antibacterial ability. Under the action of the wound electric field, the conductive property of SWCNT will generate microcurrent, thereby promoting the rapid migration of multiple cells along the electrochemical gradient. In addition, the EF@S-HGM hydrogel can activate the aging pathway of glucocorticoid receptors, promote the formation of NETs, and thus enhance the antibacterial effect. The carbon nanotube conductive hydrogel prepared by the method provided by the present invention has excellent antibacterial properties, can resist bacterial infection of wounds, and at the same time has the effect of promoting angiogenesis or tissue regeneration, achieving excellent treatment of infected wounds. And the EF@S-HGM hydrogel prepared by the present invention can be used as a tissue engineering skin, or as a regenerative medicine material, which can provide a new option for the treatment and care of infected wounds, greatly improve the treatment effect and prognosis of patients, and is expected to become a comprehensive measure for the treatment of infected wounds, provide a new treatment strategy for refractory wounds, and provide patients with an efficient, economical and convenient solution. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a physical diagram of the gelation process of preparing EF@S-HGM hydrogel in Example 1 of the present invention;
[0024] Figure 2 The scanning electron micrographs of the EF@S-HGM hydrogels prepared in Examples 1 to 3 of the present invention;
[0025] Figure 3 This is a physical picture of the injectability and self-healing ability test of the EF@S-HGM hydrogel prepared in Example 1 of the present invention, wherein the first line is the self-healing ability and the second line is the injectability;
[0026] Figure 4 This is a physical picture of the conductivity test of the EF@S-HGM hydrogel prepared in Example 1 of the present invention;
[0027] Figure 5Elemental spectra of the EF@S-HGM hydrogel prepared in Example 1 of the present invention and the EF@HGM hydrogel prepared in Comparative Example 1, wherein the first row is C, O, N and Na of the EF@HGM hydrogel, and the second row is C, O, N and Na of the EF@HGM;
[0028] Figure 6 EDS line scan images of the EF@S-HGM hydrogel prepared in Example 1 of the present invention and the EF@HGM hydrogel prepared in Comparative Example 1;
[0029] Figure 7 The pore size bar graph of the EF@S-HGM hydrogel prepared in Examples 1 to 3 of the present invention;
[0030] Figure 8 The conductivity statistics of the EF@S-HGM hydrogel prepared in Examples 1 and 4 of the present invention and the EF@HGM hydrogel prepared in Comparative Example 1;
[0031] Fig. 9 The rheological time scan diagrams of the EF@S-HGM hydrogels prepared in Examples 1 to 3 of the present invention and the rheological time scan diagrams of the EF@S-HGM hydrogels prepared in Example 2 under cyclic low-high shear strain are shown, wherein: Fig. 9 The middle left picture is Examples 1 to 3. Fig. 9 The middle right picture is Example 2, ***P<0.001;
[0032] Fig.10 This is a schematic diagram of the mouse liver hemostasis experiment in the present invention;
[0033] Fig.11 This is a real picture of each treatment group within 60 seconds of treatment in the mouse liver hemostasis experiment of the present invention;
[0034] Fig.12 Statistical graph of blood loss after treatment in each treatment group of the present invention, wherein, scale bar: ns, not significant, ***P<0.001;
[0035] Fig.13 Statistical graph of hemolysis rate of ultrapure water, PBS, S-HGM and EF@S-HGM hydrogel prepared in Example 1 of the present invention, wherein the scale bar: ns, not significant, ***P<0.001;
[0036] Fig.14 HE staining images of the heart, liver, spleen, lung and kidney of mice injected with methacrylate gelatin (MeGel), HGM, S-HGM and EF@S-HGM hydrogel prepared in Example 1, respectively;
[0037] Fig.15Live / dead staining images of methacrylate gelatin, HGM, S-HGM in the present invention and EF@S-HGM hydrogel prepared in Example 1 after being cultured with HL-60 for 1, 2 and 3 days respectively;
[0038] Fig.16 Live / dead staining images of gelatin, HGM, S-HGM in the present invention and EF@S-HGM hydrogel prepared in Example 1 after being cultured with HUVEC for 1, 2 and 3 days respectively;
[0039] Fig.17 Schematic diagram of the co-culture system and the bacterial coating co-culture solution of the present invention;
[0040] Fig.18 The physical pictures and electron microscope pictures of PBS, LPS, EF@S-HGM hydrogel prepared in Example 1 and EF@S-HGM hydrogel containing mifepristone in the present invention, respectively, after being cultured with MRSA aureus and Escherichia coli for 12 hours;
[0041] Fig.19 The colony counts of PBS, LPS, EF@S-HGM hydrogel prepared in Example 1, and EF@S-HGM hydrogel containing mifepristone after culturing with MRSA aureus and Escherichia coli for 12 hours are shown in the figure. Fig.19 As shown;
[0042] Fig. 20 The statistical diagram of the bacterial structure damage rate after culturing PBS, LPS, EF@S-HGM hydrogel prepared in Example 1 and EF@S-HGM hydrogel containing mifepristone with MRSA aureus and Escherichia coli for 12 hours ( Fig.19 and Fig. 20 All results are expressed as mean ± SD, n = 3, *P < 0.05, **P < 0.01, ***P < 0.001);
[0043] Fig.21 Schematic diagram of the mouse infected wound model and the injection of EF@S-HGM hydrogel in the present invention;
[0044] Fig. 22 The overall physical pictures of wound closure of the mouse infectious wound model in the present invention on days 0, 3, 6, 9 and 12 after being treated with the control group, MRSA group, S-HGM+MRSA group and EF@S-HGM+MRSA group respectively;
[0045] Fig.23It is a line graph showing the change of wound area percentage over time in the mouse infectious wound model of the present invention after being treated with the control group, MRSA group, S-HGM+MRSA group and EF@S-HGM+MRSA group respectively;
[0046] Fig.24 The figures are the hematoxylin-eosin (HE) and Masson staining images of the wounds of the mouse infectious wound model in the present invention after being treated by the control group, MRSA group, S-HGM+MRSA group and EF@S-HGM+MRSA group respectively;
[0047] Fig.25 The collagen area percentage statistical graph of the wounds of the mouse infectious wound model in the present invention after being treated by the control group, MRSA group, S-HGM+MRSA group and EF@S-HGM+MRSA group respectively;
[0048] Fig.26 The relative wound width statistics of the wounds in the mouse infectious wound model of the present invention after being treated by the control group, MRSA group, S-HGM+MRSA group and EF@S-HGM+MRSA group respectively;
[0049] Fig. 27 CD31 immunohistochemistry, GR / MPO and CitH3 / MPO immunofluorescence images of wounds in the mouse infected wound model of the present invention after being treated by the control group, MRSA group, S-HGM+MRSA group and EF@S-HGM+MRSA group respectively;
[0050] Fig.28 The relative proportion of stained tissues of the wounds in the mouse infectious wound model of the present invention after being treated by the control group, MRSA group, S-HGM+MRSA group and EF@S-HGM+MRSA group respectively;
[0051] Fig.29 This is the preparation of EF@S-HGM hydrogel in the present invention and its mechanism of promoting the healing of infected wounds. DETAILED DESCRIPTION
[0052] The present invention provides a method for preparing a carbon nanotube conductive hydrogel, comprising the following steps:
[0053] (1) mixing β-CD, an organic solvent and triethanolamine, cooling the mixture, adding acrylic acid, and sequentially performing first stirring, filtering and concentrating to obtain a concentrated solution;
[0054] The concentrated solution is dripped into acetone and subjected to post-treatment to obtain acrylic acid-modified cyclodextrin, also known as Ac-β-CD;
[0055] (2) mixing the Ac-β-CD obtained in step (1) with gelatin and PBS to obtain a mixed solution;
[0056] (3) adding an endothelial cell growth supplement and N-formyl-Met-Leu-Phe to the mixed solution obtained in step (2), and shaking to obtain an EF@HGM solution;
[0057] The EF@HGM solution and the single-walled carbon nanotubes are mixed, and an EF@S-HGM solution is obtained by a second stirring;
[0058] (4) The EF@S-HGM solution obtained in step (3) is sequentially subjected to pH adjustment, ultrasonication, debubbling, addition of an initiator and photocuring to obtain a carbon nanotube conductive hydrogel, also known as an EF@S-HGM hydrogel.
[0059] In the present invention, unless otherwise specified, the raw materials used are conventional commercial products in the art.
[0060] The invention mixes β-CD, an organic solvent and triethanolamine, cools the mixture, adds acrylic acid, and sequentially performs first stirring, filtering and concentrating to obtain a concentrated solution.
[0061] In the present invention, the organic solvent is preferably at least one of DMF and acetone.
[0062] In the present invention, the ratio of the mass of β-CD, the volume of triethanolamine and the volume of acrylic acid is preferably 10g: (3-12)mL: (3-8mL), and more preferably 10g: 7mL: 5mL. The present invention controls the ratio of the mass of β-CD, the volume of triethanolamine and the volume of acrylic acid within the above range to facilitate the acrylic acid to fully modify the β-CD, thereby obtaining acrylic acid-modified cyclodextrin with high yield and quality.
[0063] In the present invention, the cooling is preferably cooling to a system temperature of 0°C.
[0064] The present invention has no particular restrictions on the first stirring method, and the components can be uniformly mixed using a technical solution well known in the art. The present invention has no particular restrictions on the filtering method, and solid-liquid separation can be achieved. In the present invention, the concentration method is preferably vacuum rotary evaporation to 1 / 10 times the original volume.
[0065] After obtaining the concentrated solution, the present invention drips the concentrated solution into acetone and obtains acrylic acid modified cyclodextrin, also known as Ac-β-CD after post-treatment.
[0066] In the present invention, the post-treatment preferably includes washing and vacuum drying.
[0067] In the present invention, the washing is preferably acetone washing for 2 to 5 times; the vacuum drying time is preferably 2 to 4 days.
[0068] After obtaining Ac-β-CD, the present invention mixes the Ac-β-CD with gelatin and PBS to obtain a mixed solution.
[0069] In the present invention, the concentration of gelatin in the mixed solution is preferably 5 to 12 wt %, and the concentration of Ac-β-CD in the mixed solution is preferably 3 to 20 wt %. The present invention controls the concentration of gelatin and the concentration of Ac-β-CD in the mixed solution within the above range to adjust the gel properties of the EF@S-HGM hydrogel, so that it can be injected in situ and achieve a good gel effect on the wound surface.
[0070] After obtaining the mixed solution, the present invention adds an endothelial cell growth supplement and N-formyl-Met-Leu-Phe to the mixed solution, and obtains an EF@HGM solution after shaking;
[0071] In the present invention, the concentration of the endothelial cell growth supplement in the EF@HGM solution is preferably 0.01-0.03wt%; the concentration of N-formyl-Met-Leu-Phe in the EF@HGM solution is preferably 0.001-0.003wt%. The present invention controls the concentrations of the endothelial cell growth supplement and N-formyl-Met-Leu-Phe in the EF@HGM solution within the above range to promote the subsequent preparation of the EF@S-HGM hydrogel to recruit neutrophils and enhance NETosis, thereby fighting against microbial pathogens, thereby improving the healing of infected wounds.
[0072] In the present invention, the oscillation temperature is preferably 34-42°C; the oscillation time is preferably 6-15 minutes. The present invention fully mixes the EF@S-HGM hydrogel solution by oscillation, thereby increasing the stability of each component in the hydrogel and prolonging its degradation rate.
[0073] After obtaining the EF@HGM solution, the present invention mixes the EF@HGM solution with single-walled carbon nanotubes, and obtains an EF@S-HGM solution by a second stirring;
[0074] In the present invention, the concentration of single-walled carbon nanotubes in the EF@S-HGM solution is preferably 0.5-4 mg / mL. The present invention controls the concentration of single-walled carbon nanotubes in the EF@S-HGM solution within the above range, so that the subsequently prepared EF@S-HGM hydrogel can rely on endogenous electric fields to recruit multiple cells and enhance the proliferation and differentiation of certain stem cells.
[0075] The present invention promotes the full mixing of the EF@HGM solution and the single-walled carbon nanotubes through the second stirring.
[0076] After obtaining the EF@S-HGM solution, the present invention sequentially adjusts the pH, ultrasonicates, removes bubbles, adds an initiator, and photocures the EF@S-HGM solution to obtain a carbon nanotube conductive hydrogel, also called an EF@S-HGM hydrogel.
[0077] In the present invention, the pH is preferably adjusted to 7.2 to 7.6, more preferably to 7.4. In the present invention, the reagents used to adjust the pH are preferably sodium hydroxide solution and dilute hydrochloric acid. The present invention adjusts the pH to maintain the activity of drugs and cells in the hydrogel, which is beneficial to release drugs and recruit cells.
[0078] In the present invention, the ultrasound treatment is preferably carried out in an ice bath at 150 W for 8 to 14 minutes. The present invention uses ultrasound to fully mix the single-walled carbon nanotubes in the hydrogel solution, which is beneficial to improving the conductive properties of the hydrogel.
[0079] In the present invention, the method of removing bubbles is preferably centrifugation at 500-800 rpm for 3-8 minutes.
[0080] In the present invention, the initiator is preferably at least one of I2959 and phenyl (2,4,6-trimethylbenzoyl) phosphate lithium salt.
[0081] In the present invention, the photocuring is preferably performed under 365 nm ultraviolet light for 8 to 14 min, more preferably under 365 nm ultraviolet light for 10 min.
[0082] The present invention also provides a carbon nanotube conductive hydrogel prepared by the preparation method described in the above technical solution.
[0083] The present invention also provides the use of the carbon nanotube conductive hydrogel described in the above technical solution in the preparation of regenerative medicine materials.
[0084] In the present invention, the regenerative medicine material is preferably an artificial tissue for treating infected wounds.
[0085] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0086] Example 1
[0087] A method for preparing carbon nanotube conductive hydrogel, comprising the following steps:
[0088] (1) 10 g of β-CD was added to 150 mL of DMF, and then 7 mL of TEA was added. The mixture was stirred and cooled to 0°C. Then, 5 mL of acrylic acid was added to the solution. After the first stirring was performed for 12 h, the mixture was filtered to remove trimethylamine hydrochloride. The transparent solution obtained by filtration was concentrated to 20 mL (i.e., 1 / 10 times of the original volume) by vacuum rotary evaporation to obtain a concentrated solution. The concentrated solution was then dropped into 600 mL of acetone to precipitate acrylic acid-modified cyclodextrin. The precipitate was washed with acetone several times and vacuum dried for 3 days to obtain acrylic acid-modified cyclodextrin, also known as Ac-β-CD.
[0089] (2) dissolving the Ac-β-CD obtained in step (1) and gelatin in PBS at 37° C. to obtain a mixed solution;
[0090] The concentration of gelatin in the mixed solution is 8wt%, and the concentration of Ac-β-CD in the mixed solution is 5wt%;
[0091] (3) adding 100 μg of ECGS and 10 ng of FMLP (purchased from SigmaAldrich) to the mixed solution obtained in step (2), and shaking thoroughly at 37° C. for 10 minutes until dissolved to obtain an EF@HGM solution;
[0092] The concentration of the endothelial cell growth supplement in the EF@HGM solution is 0.01wt%; the concentration of N-formyl-Met-Leu-Phe in the EF@HGM solution is 0.001wt%;
[0093] The EF@HGM solution and single-walled carbon nanotubes SWCNT (diameter 0.8-1.2 nm; length 100-1000 nm, purchased from Engineering ForLife) were mixed, and an EF@S-HGM solution was obtained by a second stirring;
[0094] The concentration of single-walled carbon nanotubes in the EF@S-HGM solution is 1 mg / mL;
[0095] (4) The EF@S-HGM solution obtained in step (3) was adjusted to a pH of 7.4 with sodium hydroxide solution and dilute hydrochloric acid, and then subjected to ultrasonic treatment at 150W for 10min in an ice bath to uniformly disperse the SWCNT in the solution, and then centrifuged at 600rpm for 5min to remove bubbles, and then 0.05wt% of initiator I2959 was added, and the mixture was transferred into a PVC mold at 37°C, cooled to 25°C, and then irradiated with 365nm ultraviolet light (UV) for 10 minutes (10mW / cm 2 ) to obtain EF@S-HGM hydrogel.
[0096] Embodiment 2, 3
[0097] EF@S-HGM hydrogel was prepared according to the method of Example 1, except that the concentration of Ac-β-CD in the mixed solution in step (2) of Examples 2 and 3 was 10 wt % and 15 wt %.
[0098] Example 4
[0099] EF@S-HGM hydrogel was prepared according to the method of Example 1, except that the concentration of single-walled carbon nanotubes in the EF@S-HGM solution in step (3) of Example 4 was 2 mg / mL.
[0100] Comparative Example 1
[0101] The preparation method of EF@HGM hydrogel comprises the following steps:
[0102] The preparation was carried out according to the method of Example 1, except that the concentration of single-walled carbon nanotubes in the EF@S-HGM solution in step (3) of Comparative Example 1 was 0 mg / mL.
[0103] Figure 1 This is a physical diagram of the gelation process of preparing EF@S-HGM hydrogel in Example 1 of the present invention.
[0104] Figure 2 The scanning electron micrographs of the EF@S-HGM hydrogels prepared in Examples 1 to 3 are shown in FIG. Figure 2 It can be seen that the Ac-β-CD content is positively correlated with the number of micropores in EF@S-HGM hydrogel.
[0105] The injectability and self-healing ability test of the EF@S-HGM hydrogel prepared in Example 1 were obtained by shear viscosity test and pressure strain test. Figure 3 As shown, the first line represents the self-healing ability and the second line represents the injectability. Figure 3 It can be seen that at 37°C, the EF@S-HGM hydrogel healed after being cut and contacted, and was sucked up with a syringe with an 18G needle and then injected into a Y-shaped mold to obtain a Y-shaped hydrogel to achieve remodeling. This shows that the EF@S-HGM hydrogel exhibits excellent self-healing and injectable properties at 37°C, proving the stability of its host-guest cross-linking. Traditional injectable hydrogels usually require the preparation of precursor solutions in advance and immediate injection, and also require the formation of hydrogels in situ through chemical cross-linking or physical action (such as thermal resonance hydrogels). It can be stored under culture conditions and can be injected into the skin in the form of a gel at a specified time. This will bring great benefits to doctors and patients and greatly speed up clinical procedures. In addition, by Figure 3It can be seen that the EF@S-HGM hydrogel of the present invention can still maintain the "gel" state after passing through the narrow needle tip (18G needle) and conform to the geometric shape of the injection site. This property is consistent with the deformation trend of human skin during strain and bending, avoiding potential damage caused by diffusion or leakage of injected materials to other locations, thereby achieving precise drug delivery. In addition, the above-mentioned shear viscosity experiment and pressure strain experiment also illustrate the excellent rheological properties of the EF@S-HGM hydrogel prepared by the present invention, which enables it to withstand multiple compressions and stretching without damage. This property is crucial to the integrity of the hydrogel when implanted in traumatic sites (such as the sole or joints and other weight-bearing sites).
[0106] Figure 4 This is a physical picture of the conductivity test of the EF@S-HGM hydrogel prepared in Example 1. Figure 4 It can be seen that the small light is not on when the line is disconnected, but after connecting the EF@S-HGM hydrogel, the small light becomes bright, indicating that the EF@S-HGM hydrogel prepared in Example 1 has good conductivity. It is generally believed that carbon nanotubes work by transmitting electrical signals and increasing neuronal excitability. However, carbon nanotube-hydrogel composites can recruit a variety of cells and enhance the proliferation and differentiation of certain stem cells solely by endogenous electric fields. Through the synergistic effect of van der Waals forces and electrostatic forces between the hydrogel micropores, the number of carbon nanotubes adsorbed on the pore walls will increase, and it is not easy to fall off from the pore walls. The rapid self-healing process of the EF@S-HGM hydrogel prepared by the present invention ensures the integrity of the local electric field environment and avoids the degradation of the electrical properties of SWCNT during large deformation. SWCNT has good electron transfer characteristics and can effectively improve the conductivity of the composite material at a very low level. It can increase the conductivity of the hydrogel in a dose-dependent manner, so that the EF@S-HGM hydrogel makes the light bulb glow like a wire.
[0107] The elemental spectra of the EF@S-HGM hydrogel prepared in Example 1 and the EF@HGM hydrogel prepared in Comparative Example 1 are shown in FIG. Figure 5 As shown, the first row is C, O, N and Na of EF@HGM hydrogel, and the second row is C, O, N and Na of EF@HGM. The EDS line scan is shown in Figure 6 As shown. Figure 5 and Figure 6 It can be seen that the addition of SWNCT in the present invention has no obvious effect on the microstructure of the prepared hydrogel, and confirms the uniform distribution of carbon in the EF@S-HGM hydrogel.
[0108] Figure 7 The pore size bar graph of the EF@S-HGM hydrogel prepared in Examples 1 to 3. Figure 7 It can be seen that the Ac-β-CD content is negatively correlated with the micropore size of EF@S-HGM hydrogel.
[0109] Figure 8 The conductivity statistics of the EF@S-HGM hydrogel prepared in Example 1 and Example 4 and the EF@HGM hydrogel prepared in Comparative Example 1 are shown in FIG. Figure 8 It can be seen that the EF@S-HGM hydrogel prepared in Example 4 of the present application has good conductivity, and the conductivity of the hydrogel increases with the increase of SWCNT concentration.
[0110] The present invention also studies the storage modulus (G′) and loss modulus (G″) of different hydrogels, as well as the rheological time scan under cyclic low shear strain and high shear strain. The rheological time scan of the EF@S-HGM hydrogel prepared in Examples 1 to 3 is shown in FIG. Fig. 9 As shown in the middle left figure, the rheological time scan of EF@S-HGM hydrogel prepared in Example 2 under cyclic low-high shear strain is as follows Fig. 9 As shown in the middle right figure, (gel: gelatin-8%, Ac-β-CD: 10%), ***P<0.001. Fig. 9 It can be seen that the EF@S-HGM hydrogel prepared in the present invention has excellent mechanical stability.
[0111] In order to study the good biocompatibility of EF@S-HGM hydrogel, the present invention verifies it in vivo and in vitro. Fig.10 As shown in the figure, the specific operation steps are: after injecting 10% chloral hydrate to anesthetize the mouse, the mouse abdomen is cut to expose the liver; the plasma around the liver is carefully removed to avoid blood volume measurement errors; a filter paper of a predetermined weight (W0) is inserted under the liver, and the liver is pierced with an 18g needle for bleeding; then the EF@S-HGM hydrogel prepared in Example 1 is injected into the wound, and no treatment is performed as a negative control group, and the hemostatic sponge group is used as a positive control; then, the liver wound is photographed at 0, 5, 15, 30 and 60 seconds, and the weight of the blood-accumulating filter paper (W1) is weighed after 60 seconds.
[0112] The actual pictures of each treatment group within 60 seconds of treatment in the mouse liver hemostasis experiment of the present invention are as follows Fig.11 As shown in the figure, the statistical graph of blood loss in each treatment group after treatment is as follows Fig.12 Shown, where scale bars: ns, not significant, ***P < 0.001.
[0113] Depend on Fig.11 and Fig.12 It can be seen that injecting the EF@S-HGM hydrogel prepared in Example 1 into the liver wound of mice can reduce blood loss, which indicates that the EF@S-HGM hydrogel can promote blood coagulation.
[0114] The hemolysis rate statistics of ultrapure water, PBS, S-HGM and EF@S-HGM hydrogel prepared in Example 1 were obtained by spectrophotometer. Fig.13 As shown, where scale bars: ns, not significant, ***P<0.001. Fig.13 It can be seen that EF@S-HGM hydrogel does not cause hemolysis. Therefore, the EF@S-HGM hydrogel prepared in the present invention can be used not only for wounds with severe bleeding, but also for wounds that have just healed.
[0115] In order to further study the toxicity of the EF@S-HGM hydrogel prepared in the present invention on major organs, we injected methacrylate gelatin (MeGel), HGM, S-HGM and the EF@S-HGM hydrogel prepared in Example 1 into different infected wounds of mice, and obtained HE staining images of the heart, liver, spleen, lung and kidney of the mice injected with methacrylate gelatin (MeGel), HGM, S-HGM and the EF@S-HGM hydrogel prepared in Example 1, as shown in the figure. Fig.14 As shown. Fig.14 It can be seen that there were no obvious changes in the heart, liver, spleen, lungs and kidneys of the mice.
[0116] Live / dead cell staining experiment: (1) Methacrylate gelatin, HGM, S-HGM and EF@S-HGM hydrogel prepared in Example 1 were cultured with HL-60 for 1, 2 and 3 days, and then live / dead staining was performed to obtain live / dead staining images of gelatin, HGM, S-HGM and EF@S-HGM hydrogel prepared in Example 1 after being cultured with HL-60 for 1, 2 and 3 days, respectively. Fig.15 (2) After culturing methacrylate gelatin, HGM, S-HGM and the EF@S-HGM hydrogel prepared in Example 1 with HUVEC for 1, 2 and 3 days, live / dead staining was performed to obtain live / dead staining images of the gelatin, HGM, S-HGM and the EF@S-HGM hydrogel prepared in Example 1 with HUVEC for 1, 2 and 3 days, respectively. Fig.16 shown.
[0117] In the early stages of wound healing, neutrophils are one of the first immune cells to be recruited to the site of inflammation. They have the ability to resist bacterial proliferation and remove tissue debris. HUVECs are indispensable cells in the entire process of wound repair, and their degree of vascularization greatly affects wound healing. The above live and dead cell staining experiment results, Fig.15 and Fig.16 The results showed that human promyelocytic leukemia cells (HL-60) and HUVEC encapsulated in EF@S-HGM hydrogels were able to contact the surrounding hydrogel matrix and they maintained their viability to a large extent (viability > 95%).
[0118] In order to evaluate the in vitro antibacterial ability of the EF@S-HGM hydrogel prepared by the present invention, the present invention conducted an in vitro antibacterial performance test experiment, specifically: HL-60 cells in serum-free 1640 culture medium were added to the upper chamber of the Transwell, and then PBS, LPS, EF@S-HGM hydrogel prepared in Example 1, and EF@S-HGM hydrogel containing mifepristone were added to the upper chamber of the Transwell system. A PBS solution containing 1% FBS was injected into the lower chamber. Electrodes were inserted at both ends of the hydrogel, and the voltage was set to 25mV to simulate the micro-electric field in the trauma. The transwell system with a pore size of 0.4μm prevents neurons from passing through, but allows NETs to migrate freely to the lower chamber. In order to offset the chemotactic effect of EF@S-HGM hydrogel on the NET in the upper chamber, we also added EF@S-HGM hydrogel to the lower chamber. After 4 hours of migration, the lower chamber solution containing NETs was co-cultured with bacteria to test its antibacterial ability.
[0119] The schematic diagram of the co-culture system and the bacterial coating co-culture solution of the present invention is as follows Fig.17 shown.
[0120] The morphology of Staphylococcus aureus and Escherichia coli under different treatments was observed using a scanning electron microscope, and the physical images and electron microscope images of PBS, LPS, EF@S-HGM hydrogel prepared in Example 1, and EF@S-HGM hydrogel containing mifepristone in the present invention cultured with MRSA Staphylococcus aureus and Escherichia coli for 12 hours were obtained. Fig.18 As shown in the figure, the colony count statistics are as follows Fig.19 As shown in the figure, the statistical diagram of bacterial structure damage rate is as follows Fig. 20 As shown, Fig.19 and Fig. 20 All results are expressed as mean ± SD, n = 3, *P < 0.05, **P < 0.01, ***P < 0.001. Figures 18 to 20 The results showed that the EF@S-HGM hydrogel group had excellent antibacterial ability, with the inhibition rates against methicillin-resistant Staphylococcus aureus (MRSA) and Escherichia coli (E.coli) being 96.7% and 98.8%, respectively. Fig.19 and 20 ).like Fig.18 and 20 As shown, the supernatant of HL-60 treated with EF@S-HGM hydrogel severely damaged the cell walls of S. aureus and E. coli compared with those treated with PBS and LPS, while the addition of mifepristone largely alleviated this damaging effect.
[0121] After verifying in vitro that EF@S-HGM hydrogel has significant antibacterial activity and promotes wound healing, in order to study whether the EF@S-HGM hydrogel prepared by the present invention can promote the healing of infected wounds in vivo, a mouse infected wound model was established to test whether it can accelerate the healing of infected wounds in vivo ( Fig.21 ), the specific steps are as follows: 3 mice per group, after depilation of the dorsal side of each C57 / 6J mouse, the entire skin layer was excised along a circle with a diameter of 1 cm in the middle of the back. The wound area was photographed and measured on days 0, 3, 6, 9 and 12 ( Fig. 22 and 23 ). Full-thickness wounds on the backs of mice were bandaged with MeGel hydrogel containing PBS (control group), MeGel hydrogel containing MRSA (MRSA group), S-HGM hydrogel containing MRSA (S-HGM+MRSA group), and EF@S-HGM hydrogel containing MRSA (EF@S-HGM+MRSA group), respectively. No animals died or showed abnormal signs after surgery on day 0. During the inflammatory stage (days 3 and 6), the bacterial scabs after wound healing in the infected mice in the MRSA group were more obvious than those in the other groups, indicating that the presence of bacteria significantly prolonged the inflammatory stage of wound healing. During the repair stage (days 9 and 12), the wounds of mice in the MRSA group healed slowly, while treatment with EF@S-HGM hydrogel significantly accelerated the wound healing process. Twelve days after injury, in addition to directly monitoring the wound area, various histological experiments were performed to explore the characteristics of the wound tissue.
[0122] The schematic diagram of the mouse infected wound model and the injection of EF@S-HGM hydrogel in the present invention is shown in Fig.21 shown.
[0123] The overall physical pictures of wound closure on days 0, 3, 6, 9 and 12 of the mouse infected wound model in the present invention after treatment with the control group, MRSA group, S-HGM+MRSA group and EF@S-HGM+MRSA group are as follows: Fig. 22 As shown in Figure 2, the line graph of wound area percentage changes over time is as follows: Fig.23 shown.
[0124] The wounds of the mouse infected wound model in the present invention were treated with the control group, MRSA group, S-HGM+MRSA group and EF@S-HGM+MRSA group respectively. The hematoxylin-eosin (HE) and Masson (Masson) staining images are as follows: Fig.24 As shown in the figure, the collagen area ratio statistics are as follows Fig.25 As shown in the figure, the relative wound width statistics are as follows Fig.26 shown.
[0125] Depend on Figures 22 to 26It can be seen that among the mice with infected wounds on the 12th day after injury, the scar width of the EF@S-HGM+MRSA group was the narrowest, almost reaching the level of the control group, followed by the S-HGM+MRSA group ( Fig.26 ). Masson staining was used to examine the effects on collagen deposition and remodeling, especially in the EF@S-HGM+MRSA group, which showed enhanced collagen deposition and regular arrangement on day 12. In contrast, the wounds in the MRSA group were infiltrated with inflammatory cells and had a disorganized appearance.
[0126] During wound healing, the formation of new blood vessels is crucial for delivering nutrient factors to the wound site. Therefore, the present invention next investigated whether EF@S-HGM hydrogel treatment could promote angiogenesis at the wound site.
[0127] The CD31 immunohistochemistry, GR / MPO and CitH3 / MPO immunofluorescence images of the mouse infected wound model after treatment with the control group, MRSA group, S-HGM+MRSA group and EF@S-HGM+MRSA group are shown in the following figure: Fig. 27 As shown, the expression levels of GR, CitH3 and MPO in wound tissue were also analyzed, and the relative proportion of stained tissue was obtained as shown in Fig.28 As shown (where Fig.23 , 25 , 26 and 28, scale bars: 500 μm, 200 μm, 200 μm. All results are expressed as mean ± SD, n = 3, *p < 0.05; **p < 0.01; ***p < 0.001).
[0128] Depend on Fig. 27 and 28 It can be seen that more CD31-labeled blood vessels were observed in the EF@S-HGM+MRSA group compared with the MRSA group. To explore the effect of EF@S-HGM hydrogel on neutrophils in vivo, immunofluorescence detection of GR, CitH3, and MPO was performed. Consistent with the results of in vitro experiments, neutrophils were detected in the EF@S-HGM group, which was significantly different from the MRSA group. These findings suggest that EF@S-HGM hydrogel can help infected wounds heal through multiple mechanisms such as collagen deposition, angiogenesis, and NETosis.
[0129] Fig.29 The preparation of EF@S-HGM hydrogel in the present invention and its mechanism of promoting healing of infected wounds, wherein: Fig.29 A in the middle shows the EF@S-HGM hydrogel injected into the infected wound of a rat with an infected wound surface. Fig.29 Figure B is the preparation process of EF@S-HGM hydrogel. Fig.29C in the middle indicates that under the action of the wound electric field, the conductive property of SWCNT in EF@S-HGM hydrogel will generate microcurrent, thereby promoting the migration of Neu and HUVEC, as well as the antibacterial ability of NETosis and Neu. Fig.29 D in the middle shows that EF@S-HGM hydrogel activates glucocorticoid receptor, and Neu forms NET through the GR aging pathway.
[0130] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing carbon nanotube conductive hydrogel, characterized in that: The following steps are involved: (1) mixing β-CD, an organic solvent and triethanolamine, cooling the mixture, adding acrylic acid, and sequentially performing first stirring, filtering and concentrating to obtain a concentrated solution; The concentrated solution is dripped into acetone and subjected to post-treatment to obtain acrylic acid-modified cyclodextrin, also known as Ac-β-CD; (2) mixing the Ac-β-CD obtained in step (1) with gelatin and PBS to obtain a mixed solution; (3) adding an endothelial cell growth supplement and N-formyl-Met-Leu-Phe to the mixed solution obtained in step (2), and shaking to obtain an EF@HGM solution; The EF@HGM solution and the single-walled carbon nanotubes are mixed, and an EF@S-HGM solution is obtained by a second stirring; (4) The EF@S-HGM solution obtained in step (3) is sequentially subjected to pH adjustment, ultrasonication, debubbling, addition of an initiator and photocuring to obtain a carbon nanotube conductive hydrogel, also known as an EF@S-HGM hydrogel.
2. The preparation method according to claim 1, characterized in that: In the step (1), the ratio of the mass of β-CD to the volume of triethanolamine is 10 g: (3-12) mL.
3. The preparation method according to claim 1, characterized in that: The post-treatment in step (1) comprises washing and vacuum drying in sequence.
4. The preparation method according to claim 1, characterized in that: In the step (2), the concentration of gelatin in the mixed solution is 5-12 wt %, and the concentration of Ac-β-CD in the mixed solution is 3-20 wt %.
5. The preparation method according to claim 1, characterized in that: The oscillation temperature in step (3) is 34-42° C., and the oscillation time is 6-15 min.
6. The preparation method according to claim 1, characterized in that: The concentration of single-walled carbon nanotubes in the EF@S-HGM solution in step (3) is 0.5-4 mg / mL.
7. The preparation method according to claim 1, characterized in that: The pH adjustment in step (4) is to adjust the pH value of the EF@S-HGM solution to 7.2-7.
6.
8. The preparation method according to claim 1, characterized in that: The light curing in step (4) is performed by irradiating with 365 nm ultraviolet light for 8 to 14 minutes.
9. The carbon nanotube conductive hydrogel prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the carbon nanotube conductive hydrogel according to claim 9 in preparing regenerative medicine materials.